2020
DOI: 10.1111/pcmr.12918
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensives and melanoma: An updated review

Abstract: Antihypertensive medications are commonly prescribed and well-studied. Given the widespread use and potential side effects, various theories have been made about the relationship between antihypertensives and malignancy, including melanoma. This review describes the current understanding of the most commonly prescribed antihypertensives and their associations with melanoma. The literature demonstrates that diuretics, specifically hydrochlorothiazide and indapamide, may increase the risk of melanoma. While ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…Researchers have proposed several theories to interpret their therapeutic effects in various dermatoses [ 7 ]. In general, they may inhibit angiogenesis in dermatoses of vascular origin, such as rosacea [ 8 ], inhibit β-adrenergic receptors in melanocytes, and slow tumor growth in dermatoses of non-vascular origin, such as melanoma [ 9 ], and may also promote wound healing [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have proposed several theories to interpret their therapeutic effects in various dermatoses [ 7 ]. In general, they may inhibit angiogenesis in dermatoses of vascular origin, such as rosacea [ 8 ], inhibit β-adrenergic receptors in melanocytes, and slow tumor growth in dermatoses of non-vascular origin, such as melanoma [ 9 ], and may also promote wound healing [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…The trend of increasing CM incidence world-wide evokes the question of whether there are additional risk factors other than UV radiation. An association between commonly used drugs and risk for CM has been reported [ 25 , 26 , 27 ]. Some medications have secondary immuno-modulating effects in mouse models and human cell lines, but the clinical impact has to be validated [ 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation regarding these divergent results was suggested by the study of Wrobel and Le Gal which outlined the effect of non-cardioselective beta-blockers such as propranolol that can inhibit both β1 and β2 adrenoreceptors in comparison with cardioselective beta-blockers that act only on β1-adrenoreceptors. Propranolol is considered to have an important role in the inhibition of melanoma growth by modulating angiogenesis, tumor proliferation, and cell survival [ 92 ]. Studies have shown that propranolol induces a decrease in tumor development and angiogenesis, both in primary tumors and metastatic ones, and also reduces the myeloid cell infiltration of primary tumors [ 93 , 94 , 95 ].…”
Section: Neurotransmitters and Melanomamentioning
confidence: 99%